Uruk, Irak: Feldforschungen und Aufarbeitung von Grundlagendaten Konservierungsarbeiten in der Uruk-Warka- Sammlung des DAI an der Universität Heidelberg - van Ess, Margarete (e-Forschungsberichte des DAI, 2023)
In 2015 fieldwork was resumed at Uruk (Province al-Muthanna in Southern Iraq), and this for the first time since 2002. Fortunately, the site – which has been a focus of German scholars for more than a century – was well-protected by efforts of its devoted guard and the local Police for Antiquities. Be this as it may, the long absence of specialists from the site means that several structures are currently in need of intensive conservation measures. Additionally, a proposal put forward by the Iraqi government for the application of World Heritage status has seen preparations made for the compilation of an essential site management plan. First fieldwork at Uruk by the Orient Department has been devoted to a survey in the suburbs of the ancient town as well as to preparations for conservation measures.